STAIR DESIGN AND FLOOR HEIGHT DIFFERENCES IN RELATION TO SAFETY CONCEPTS FOR ELEMENTARY SCHOOL STUDENTS - Muhammad, Infaroyya Al Karimah; Sufianto, Heru; Titisari, Ema Yunita (International Journal of Social Service and Research, 2024)
The need for safe school buildings is further emphasized by the impact of natural disasters, which shows the importance of prioritizing investment in school infrastructure. This study aims to evaluate the suitability of the dimensions of the stairs with student anthropometry, regarding safety aspects in daily use, and provide design improvements to improve the safety of children in the school environment. This research is a descriptive-evaluative qualitative case study at SDN Ketawanggede from August 2023 to May 2024. Data were collected through observation, interviews, and document analysis. The results show that there are disparities in the implementation of safety and accessibility standards in schools with varying infrastructure conditions, focusing on both urban and rural areas, to identify disparities and best practices. The long-term impact of implementing safety measures, such as anti-slip materials, consistent step dimensions, and improved ramps, on the incidence of accidents and injuries among students, is analyzed. The practical outcome of this research includes actionable design solutions to mitigate safety hazards, particularly addressing differences in school floor heights and staircase dimensions. The study provides a valuable resource for policymakers, school administrators, and architects involved in designing and maintaining school facilities.